2022
DOI: 10.3390/vaccines10050695
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination in Multiple Sclerosis and Inflammatory Diseases: Effects from Disease-Modifying Therapy, Long-Term Seroprevalence and Breakthrough Infections

Abstract: Background: To determine the effect of disease-modifying therapies (DMT) on humoral postvaccine seroconversion, long-term humoral response, and breakthrough COVID-19 infections in persons with multiple sclerosis (PwMS) and other neuroinflammatory disorders. Methods: A total of 757 PwMS and other neuroinflammatory disorders were recruited in two MS centers and vaccinated with one of the FDA-approved vaccines (BNT162b2, mRNA-1273, Ad26.COV2.S). The primary outcomes are the rate of humoral postvaccine seroconvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…Indeed, in our study, pwMS belonging to the depleting/sequestering-out subgroup (including alemtuzumab-, cladribine-, fingolimod- and ocrelizumab-treated) showed a significantly lower humoral response to vaccination when compared to HD and to the enriching-in subgroup (natalizumab-treated). This is in agreement with several published studies in which a pattern of low humoral response to SARS-CoV-2 vaccination, with respect to healthy subjects, has been previously reported, mainly for patients receiving B-cell depleting drugs ( 35 37 ) and fingolimod ( 32 , 38 ). Even though the depleting/sequestering-out subgroup displayed lower anti-Spike antibody titers, most patients had near-normal total anti-Spike IgG levels, while only few did not seroconvert.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, in our study, pwMS belonging to the depleting/sequestering-out subgroup (including alemtuzumab-, cladribine-, fingolimod- and ocrelizumab-treated) showed a significantly lower humoral response to vaccination when compared to HD and to the enriching-in subgroup (natalizumab-treated). This is in agreement with several published studies in which a pattern of low humoral response to SARS-CoV-2 vaccination, with respect to healthy subjects, has been previously reported, mainly for patients receiving B-cell depleting drugs ( 35 37 ) and fingolimod ( 32 , 38 ). Even though the depleting/sequestering-out subgroup displayed lower anti-Spike antibody titers, most patients had near-normal total anti-Spike IgG levels, while only few did not seroconvert.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have demonstrated that antibody responses in anti-CD20 mAb and S1P-treated patients are significantly blunted following two doses of SARS-CoV-2 vaccination 2 , 3 . Several recent prospective studies demonstrated a higher risk of breakthrough COVID-19 in vaccinated patients on these DMT classes, which was correlated with reduced spike-specific-antibody levels 4 , 5 . It is therefore imperative to determine if additional vaccinations may improve immune responses.…”
Section: Discussionmentioning
confidence: 94%
“…We and others have previously demonstrated that two classes of certain MS disease modifying therapies (DMTs), in particular anti-CD20 monoclonal antibodies (mAb) and sphingosine-1-phosphate (S1P) receptor modulators, significantly reduce spike antibody responses following the first two doses of SARS-CoV-2 vaccination 2 , 3 . The impaired responses to initial vaccination appear to result in increased risk of breakthrough COVID-19 in vaccinated MS patients on ocrelizumab, rituximab, and fingolimod 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, it has been suggested that the immune response after SARS-CoV-2 vaccination can be improved through additional booster shots ( 7 , 8 ) and by optimally adjusting vaccination timing based on the timing of immune cell repopulation after the last administration of specific immunosuppressive DMTs ( 9 ). Specifically, in contrast to the initial international recommendation for timing DMTs (msfi.org) of a 3-month waiting time after the last dose of immune-suppressive therapies, we and others have observed that a 6-month waiting time would be optimal ( 2 , 10 ).…”
Section: Introductionmentioning
confidence: 99%